Cardiac resynchronisation therapy in anthracycline-induced cardiomyopathy. Issue 4 (6th September 2021) - Patel, Divyang; Kumar, Anirudh; Moennich, Laurie Ann; Trulock, Kevin; Nemer, David M; Donnellan, Eoin; Il'Giovine, Zachary J; Martyn, Trejeeve; Callahan, Thomas D; Hussein, Ayman A; Tarakji, Khaldoun G; Kanj, Mohamed; et al.
Abstract : Introduction: Chemotherapy-induced cardiomyopathy has been increasingly recognised as patients are living longer with more effective treatments for their malignancies. Anthracyclines are known to cause left ventricular (LV) dysfunction. While heart failure medications are frequently used, some patients may need consideration for device-based therapies such as cardiac resynchronisation therapy (CRT). However, the role of CRT in anthracycline-induced cardiomyopathy (AIC) is not well understood. Methods: We performed a retrospective review of all patients undergoing CRT implantation at our centre from 2003 to 2019 with a diagnosis of AIC. The LV remodelling and survival outcomes of this population were obtained and then compared with consecutive patients with other aetiologies of non-ischaemic cardiomyopathy (NICM). Results: A total of 34 patients underwent CRT implantation with a diagnosis of AIC with a mean age of 60.5±12.7 years, left ventricular ejection fraction (LVEF) of 21.7%±7.4%, and 11.3±7.5 years and 10.2±7.4 years from cancer diagnosis and last anthracycline exposure, respectively. At 9.6±8.1 months after CRT implantation, there was an increase of LVEF from 21.8%±7.6% to 30.4%±13.0% (p<0.001). Patients whose LVEF increased by at least 10% post-CRT implant (42.5% of cohort) survived significantly longer than patients who failed to improve their LVEF by that amount (p=0.01). A propensity matched analysis between patients with AIC and 369 consecutive patients with other aetiologies of NICM who underwent CRT implantation during the same period revealed no significant differences in improvement in LVEF or long-term survival. Conclusions: Patients with AIC undergo LV remodelling with CRT at rates similar to other aetiologies of NICM. Furthermore, AIC post-CRT responders have a favourable long-term mortality compared with non-responders.